2017
DOI: 10.1016/j.heliyon.2017.e00287
|View full text |Cite
|
Sign up to set email alerts
|

miRNA signatures can predict acute liver failure in hepatitis E infected pregnant females

Abstract: BackgroundAcute viral hepatitis E (AVH-E) can often result in acute liver failure (ALF) during pregnancy. microRNAs serve as mediators in drug induced liver failure. We investigated their role as a biomarker in predicting ALF due to HEV (ALF-E).MethodsWe performed next generation sequencing and subsequent validation studies in PBMCs of pregnant (P) self limiting AVH-E, ALF due to HEV (ALF-E) and compared with AVH-E in non-pregnant (NP) females and healthy controls.FindingsEleven microRNAs were significantly ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Yamaguchi et al 13 found that miR-431 could contribute to chemotherapy resistance in human cancer. In addition, Trehanpati et al 15 found that miR-431 was significantly expressed in hepatitis E viral (HEV) infection in liver. Other studies have also explored the relationship between miR-431 and liver disease such as HCC, but whether miR-431-5p can play a part in the invasion of HCC by means of the EMT and the mechanism of how miR-431-5p reduces the EMT in HCC have not been fully explored up to now in vitro or in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Yamaguchi et al 13 found that miR-431 could contribute to chemotherapy resistance in human cancer. In addition, Trehanpati et al 15 found that miR-431 was significantly expressed in hepatitis E viral (HEV) infection in liver. Other studies have also explored the relationship between miR-431 and liver disease such as HCC, but whether miR-431-5p can play a part in the invasion of HCC by means of the EMT and the mechanism of how miR-431-5p reduces the EMT in HCC have not been fully explored up to now in vitro or in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Healthy pregnancy was found to be associated with lower miR-122 levels. Notably, pregnancy was shown to significantly reduce more than 50% of PBMC-miRNAs compared to NPR controls [35]. When healthy pregnant women were taken as controls, a different pattern emerged; serum miR-122 levels varied according to the clinical presentation.…”
Section: Discussionmentioning
confidence: 99%
“…8 Its premature form miR-450b is predominantly upregulated in liver tissue with acute hepatic failure caused by viral hepatitis E, and is associated with poor prognosis in pregnant women. 9 These studies suggest that miR-450b and miR-450b-3p may also play important roles in HCC. Previous research showed that miR-450b-3p could inhibit breast cancer proliferation by targeting the 3′UTR of human epidermal growth factor receptor 3 (HER3) mRNA.…”
Section: Introductionmentioning
confidence: 94%
“…Among numerous tumor‐associated miRNAs, miR‐450b‐3p, whose precursor (pre‐miRNA) is located on chromosome Xq26.3, has been shown to be downregulated in the liver of the Excision Repair Cross‐Complementation Group 1 ( ERCC1 )‐deficient progeroid mouse model and the old wild‐type mice, which suggests the level of miR‐450b‐3p in the liver is related to aging . Its premature form miR‐450b is predominantly upregulated in liver tissue with acute hepatic failure caused by viral hepatitis E, and is associated with poor prognosis in pregnant women . These studies suggest that miR‐450b and miR‐450b‐3p may also play important roles in HCC.…”
Section: Introductionmentioning
confidence: 99%